THE MANUFACTURE ELECTRODE PROPERTIES ON THE HYDROGEN REACTION KINETIC IN PMFC - Sitanggang, Ramli (Eksergi, 2022)
Economic and environmental issues are forcing industry to e4rlore altemative energy sources for vehicles and electronic devices. Much effort is being put into fuel cell research because tliey hold the promise of high energy density, low environmental impact, and broad applicability. Hydrogen is the main source of fuel for high performance applications with water being the only product, These attributes make the hydrogen fuel cell a practical replacement for many power sources that are inefficient and environmentally unfriendly. T'he basic functionalunit of the fuel cell is the membrane electrode assembly (MEA). The MEA is the loci where the electrochemistry occurs to produce electricity from hydrogen and oxygen. The MEA consists of the polymer membrane with an electrode adhered to either side. The electrode contains the platinum electro-catalyst dispersed on carbon black with a polymer binder. The effect of gas diffusion electrode to the perfonnance of fuel cells was studied in a single cell. Performance dependence on the intrinsic material properties rvas studied by Fuel cell test system. The interdependence between gas diffusion electrode and fuel cell performance was covered. Long-term stability of the PEMFC stack built in the l¿boratory of Advanced Energy Systems was dernonstrated by operating it continuously.